Emile/CLIL, EMI vs TCC : des espaces de recherche si proches et si lointains - Stéphanie Roussel; André Tricot (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
The aim of this paper is to focus on convergences and divergences between experimental results coming from research areas which are different although they examine the same research object ie foreign language learning, the latter being linked to the learning of a specific field. CLIL (content and language integrated learning) and EMI (English as a medium of instruction) are acronyms, which delineate research areas whose boundaries are often blurred. CLIL and EMI differ in the sense that they can use different methodologies and invoke different theoretical frameworks, but converge in the sense that they observe and analyze similar objects: the teaching-learning of a specific content in a foreign language and the teaching-learning of a foreign language through content teaching-learning. When the cognitive load theory–which is generally concerned with teaching-learning disciplinary/specific knowledge, is used as a theoretical framework and meets these areas of research, new results emerge. Do they converge or on the contrary diverge on the same object?